Perspectives on brain health and dementia prevention in Latin America: challenges and opportunities - Fox, Sarah; León, Tomás; Mariano, Luciano; Arshad, Faheem; Magrath Guimet, Nahuel; Hope, Grainne; Tituaña, Kuripacha; Zapata-Restrepo, Lina María (Frontiers in Dementia, 2023)
While age-specific dementia prevalence is falling in many countries, several recent reviews estimate prevalence in Latin America to be higher than anywhere else in the world. This may be, in part, due to the high incidence of socioeconomic and health-related risk factors present in the region. However, growing evidence suggests that primary and secondary prevention via modifiable risk factors is possible, and that 40% of cases may be mitigated through interventions which target modifiable risk. This suggests that there may be significant scope for dementia risk reduction in this region. In June 2021, eight fellows from the Global Brain Health Institute (GBHI) hosted an expert consensus workshop on challenges and opportunities for brain health and dementia prevention in Latin America. The workshop brought together 16 experts in dementia, aging, and brain health from a range of professional backgrounds and geographical regions. From this workshop we collated an expert-led consensus regarding the practical challenges and opportunities implicit in embedding brain health and dementia prevention initiatives in the Latin American context. Here we discuss the outcomes of this workshop, highlighting several challenges and opportunities and discussing how these may be addressed.